Development and Validation of an HPLC Method for Simultaneous Assay of MCI and MI in Shampoos Containing Plant Extracts - Le Thi Huong Hoa; Vo Tran Ngoc Hung; Do Thu Trang; Thai Nguyen Hung Thu; Dinh Chi Le (International Journal of Analytical Chemistry)
A simple, easy-to-implement HPLC method was developed and validated for simultaneous determination of two isothiazolinone preservatives, methylchloroisothiazolinone (MCI) and methylisothiazolinone (MI), in hair care shampoo containing plant extracts. In this method, shampoo samples were first dissolved in isopropyl myristate and then MCI and MI were extracted from isopropyl myristate layer by a mixture of methanol and 0.02 M phosphate buffer solution pH 3.0 (30: 70, v/v) and analyzed on an analytical biphenyl column maintained at 25°C with a mixture of methanol and water (10: 90, v/v) in isocratic elution mode as mobile phase. Total flow rate of mobile phase was maintained at 1.0 mL per minute. The UV detection was performed at 274 nm. Injection volume was 50 μl. The method was fully validated in terms of specificity, linearity, precision, accuracy, and robustness according to requirements of AOAC International and was proved as reliable and suitable for the intended application.